An Analytical Study of the Two Important Characters “Asrar Mian” and “Chhammi” of Novel “Aangan” - Mushtaq, Majid; Yaseen, Samiullah; Raza, Abdullah (sourcecoder, 2024)
Khadija Mastoor is well known fiction writer. She belongs to a family of writers. Her novels and short stories reflect the life with depth. Novel Nigari is a famous novel in history of Urdu literature. This article having critical approach towards its characters. Asrar Mian and Chhammi are the characters, which highlights the civilization and its different angles. After this article these characters can be analyze with their social and civic importance.